Phytochemical screening of Algerian Borago officinalis L. and evaluation of its antioxidant and antimicrobial activities against respiratory pathogens - Thanina AFIF CHAOUCHE; Arab Karim; Bendahou Mourad (International Journal of Phytomedicine, 2014)
Infectious diseases represent a serious problem of public health in countries where resistance of bacteria to antibiotics is spreading alarmingly. A such situation leads researchers to make efforts so they can isolate or synthesize new antimicrobial molecules or molecules that inhibit the resistance mechanisms. Medicinal plants can represent a rich source of such molecules. In this context, Borago officinalis L., a medicinal species which is used traditionally in Algeria to heal infectious diseases of respiratory system is studied. Both of chemical composition and biological activities was explored. GC-MS analysis of the essential oil reveals Spathulenol as the most abundant component (38.24%). HPLC applied on flavonoid’s extract shows the presence of the rutin, quercetin and spathulenol. Tests of antioxidant capacity using the DPPH and the ferric reducing methods reveal an inhibiting effect which is more important with the flavonoid’s extract. Otherwise, resistant strains to conventional antibiotics seem to be sensitive to the flavonoids with MICs varying from10.14µg/ml to 81.12µg/ml. This study indicates that Borago officinalis L. has an important antimicrobial effect, which justifies its potential use in infectious diseases. This species remains poorly investigated, further refined studies on its pure secondary metabolites are needed, in the perspective of identifying new antimicrobial molecules from this plant.